A numerical model to simulate the dynamic performance of Breathing Walls. Issue 2 (4th March 2021) - Alongi, Andrea; Angelotti, Adriana; Mazzarella, Livio
Abstract : A one-dimensional Finite Difference Model for Breathing Wall components under time dependent Dirichlet boundary conditions is presented. The algorithm undergoes a comprehensive validation against a dynamic analytical model, under either sinusoidal and generically periodic boundary conditions, adopting different airflow velocities and in relation to capacitive and resistive materials alternatively. It is found that the accurate prediction of the temperature profile inside the wall is influenced primarily by the timestep, whose optimal value can be identified through a preliminary frequency analysis of the boundary conditions. Moreover, for a better prediction of the surface heat flow density, and especially in insulating materials, refining the space grid below 1 mm is recommended, as well as the adoption of a 3-point numerical scheme. The numerical model is finally tested against experimental data on a porous concrete wall, showing that numerical errors may compare to other sources of uncertainties, regarding materials properties and boundary conditions.